An Update on Local Universality Limits for Correlation Functions Generated by Unitary Ensembles - Lubinsky, D.S. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
We survey the current status of universality limits for m-point correlation functions in the bulk and at the edge for unitary ensembles, primarily when the limiting kernels are Airy, Bessel, or Sine kernels. In particular, we consider underlying measures on compact intervals, and fixed and varying exponential weights, as well as universality limits for a variety of orthogonal systems. The scope of the survey is quite narrow: we do not consider β ensembles for β≠2, nor general Hermitian matrices with independent entries, let alone more general settings. We include some open problems.